High-on-treatment platelet reactivity predicts adverse outcome after carotid artery stenting: A prospective study. Issue 222 (February 2023) - Simonte, G.; Guglielmini, G.; Falcinelli, E.; Isernia, G.; Mezzasoma, A.M.; Gresele, P.; Lenti, M.
Abstract: Background and purpose: High-on-treatment platelet reactivity (HTPR) has been established as a predictor of major adverse cardiovascular events (MACE) in patients undergoing percutaneous coronary interventions on dual antiplatelet therapy (DAPT), but no data are available on its predictive value in patients on DAPT after carotid artery stenting (CAS). We aimed to evaluate the possible association between HTPR in patients on aspirin plus clopidogrel therapy after CAS and subsequent MACE. Methods: All consecutive patients treated with CAS in a single institution were enrolled in a prospective clinical study. HTPR was evaluated with 5 different laboratory assays carried out just before CAS. MACE incidence (cerebral ischemia, myocardial infarction, stent thrombosis, acute limb ischemia and vascular death) was evaluated at 30 days and thereafter at yearly visits. Results: A total of 300 patients were enrolled in the study, and eight were then excluded because blood samples resulted unsuitable for the laboratory testing or CAS aborted for technical problems. Median follow-up was 5.8 years and during this period 47 MACE occurred. HTPR detected by multiplate electronic aggregometry (MEA) and the VASP phosphorylation assay (VASP) were associated with a significantly enhanced risk of MACE (p = 0.048 and p = 0.038, respectively). However, HTPR to three tests (HTPR3) was more strongly predictive of increased risk of a vascular event at follow up (p = 0.005) at bivariate analysis and also at Cox regression multivariate analysis (p = 0.002). Conclusions: HTPR to three different assays (mainly to VASP + PFA P2Y+ VerifyNow) in patients on DAPT after CAS has predictive value for subsequent MACE. Prospective studies to assess whether platelet function testing-guided antiplatelet therapy is superior to standard DAPT in patient undergoing CAS should be considered. Highlights: While the predictive value of HTPR for PCI is known no data are available for CAS. 300 patients undergoing CAS were enrolled in a prospective clinical study. HTPR to DAPT was evaluated with 5 different laboratory assays. HTPR detected by MEA and VASP test was associated with risk of MACE. HTPR to three tests was strongly predictive of increased MACE risk.